2015
DOI: 10.1002/nml.21197
|View full text |Cite
|
Sign up to set email alerts
|

What Helped Nonprofits Weather the Great Recession?

Abstract: This study examined the effectiveness of several financial strategies for nonprofit organizations in fighting the Great Recession. Using data from human services and community improvement organizations in the state of New Jersey, we tested hypotheses about the relationships between three measures of financial sustainability and various fundraising efforts and financial indicators. We found that (1) except for strong external funding relationships, funding efforts were generally not effective in enhancing finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…For example, Glisson and Martin ( 1980 ) examined the relationship between organization age, size (that is, number of total workers), average worker tenure, centralization (that is, participation in decisionmaking scale and hierarchy-of-authority scale), formalization (that is, division-of-labor and procedural specifications scales), and found a strong positive relationship between centralization and productivity. Tuckman and Chang ( 1991 ) brought attention to the financial aspect of charitable nonprofit organizations and identified a range of criteria that defines financial vulnerability, which was incorporated and articulated in subsequent studies that explain organizational demise (for example , Bielefeld 1994 ;Hager 2001 ;Hager and Galaskiewicz 2002 ;Hager and Searing 2014 ;Lin and Wang 2016 ). Other studies also examined additional variables such as competition, welfare policy, organizational resources (for example, income, technical assistance), organizational structure, or local ties in relation to organizational survival (Boehm 1996 ;Twombly 2003 ;Walker and McCarthy 2010 ).…”
Section: Conceptualization Of Organizational Sustainabilitymentioning
confidence: 99%
“…For example, Glisson and Martin ( 1980 ) examined the relationship between organization age, size (that is, number of total workers), average worker tenure, centralization (that is, participation in decisionmaking scale and hierarchy-of-authority scale), formalization (that is, division-of-labor and procedural specifications scales), and found a strong positive relationship between centralization and productivity. Tuckman and Chang ( 1991 ) brought attention to the financial aspect of charitable nonprofit organizations and identified a range of criteria that defines financial vulnerability, which was incorporated and articulated in subsequent studies that explain organizational demise (for example , Bielefeld 1994 ;Hager 2001 ;Hager and Galaskiewicz 2002 ;Hager and Searing 2014 ;Lin and Wang 2016 ). Other studies also examined additional variables such as competition, welfare policy, organizational resources (for example, income, technical assistance), organizational structure, or local ties in relation to organizational survival (Boehm 1996 ;Twombly 2003 ;Walker and McCarthy 2010 ).…”
Section: Conceptualization Of Organizational Sustainabilitymentioning
confidence: 99%
“…Research has found that in comparison with smaller organizations, larger organizations provide services on a more consistent basis, even during turbulent times (Lin and Wang, ; Ranger‐Moore ). Large size suggests that an organization has the time and resources needed to improve governance and management in addition to its day‐to‐day operations.…”
Section: Environmental and Organizational Characteristics And Good Gomentioning
confidence: 99%
“…Furthermore, the literature on financial vulnerability of NPOs has emphasized the importance of the ratio of debt to total assets, as the more in debt, the more vulnerable (Andres‐Alonso, Garcia‐Rodriguez, and Romero‐Merino ; Trussel ). In fact, higher debt ratio values had a negative impact during the financial crisis (Lin and Wang ).…”
mentioning
confidence: 99%